2016
DOI: 10.1002/ana.24656
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair pathways underlie a common genetic mechanism modulating onset in polyglutamine diseases

Abstract: ObjectiveThe polyglutamine diseases, including Huntington's disease (HD) and multiple spinocerebellar ataxias (SCAs), are among the commonest hereditary neurodegenerative diseases. They are caused by expanded CAG tracts, encoding glutamine, in different genes. Longer CAG repeat tracts are associated with earlier ages at onset, but this does not account for all of the difference, and the existence of additional genetic modifying factors has been suggested in these diseases. A recent genome‐wide association stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
186
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(207 citation statements)
references
References 41 publications
8
186
0
Order By: Relevance
“…Remarkably, suppression of somatic instability delayed the phenotype in a mouse model . In GWAS analysis of CAG repeat disorders as a whole, DNA repair genes were associated with onset age, further suggesting the importance of somatic expansion . Somatic instability may influence the rate of progression, with a coding MSH3 variant having the strongest association in a GWAS .…”
Section: Evidence For a Role Of Somatic Mutations In Neurodegenerationmentioning
confidence: 99%
“…Remarkably, suppression of somatic instability delayed the phenotype in a mouse model . In GWAS analysis of CAG repeat disorders as a whole, DNA repair genes were associated with onset age, further suggesting the importance of somatic expansion . Somatic instability may influence the rate of progression, with a coding MSH3 variant having the strongest association in a GWAS .…”
Section: Evidence For a Role Of Somatic Mutations In Neurodegenerationmentioning
confidence: 99%
“…Insights into these underlying pathways could potentially serve as a target for drug manipulation. Subsequently, genotyping of these single nucleotide polymorphisms (SNP) in patients with CAG repeat disease (consisting of 1017 SCA patients), showed a significant association between DNA repair genes and the age at onset of SCA and HD, with SNPs in FAN1, PMS2 and RRM2B reaching the lowest Pvalues [30]. It has been suggested that common genetic variants, with a significant effect size, may act as genetic modifiers in rare Mendelian conditions such as the SCAs.…”
Section: The Identification Of Genetic Modifiersmentioning
confidence: 99%
“…The integrity of FAN1 is speculated to play a role in preventing TNR expansion [30]. FAN1 is a repair nuclease that is recruited to sites of cross link damage.…”
Section: Cross Link Repairmentioning
confidence: 99%
“…In addition to KIN (24), mutations in FAN1 have been associated with predisposition to colorectal and pancreatic cancer as well as autism and schizophrenia (28)(29)(30)(31), raising the possibility that defects in ICL repair may be associated with a wide variety of diseases. In vitro studies showed that human FAN1 can degrade ICL-containing oligonucleotides past the lesion in replication-like intermediates, thereby unhooking the ICLs (32)(33)(34).…”
Section: Dna Synthesis (Tls) and The Second Strand Is Repaired By Hommentioning
confidence: 99%